PENDEKATAN DEEP LEARNING DARI SEGI PERSPEKTIF TEORI BELAJAR: ANALISIS KOGNITIF, HUMANISTIK, DAN KONSTRUKTIVISTIK - Baharuddin (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
The deep learning approach in education is a learning strategy oriented towards deep conceptual understanding, reflective, and integrative. This research aims to analyze the deep learning approach from the perspective of three main learning theories namely cognitive, humanistic, and constructivistic. The deep learning approach is considered relevant in facing the challenges of 21st century education because it focuses on deep conceptual understanding, critical thinking skills, and active involvement of learners in the learning process. However, the implementation of this approach is often not supported by a strong theoretical understanding. Therefore, this research uses a descriptive qualitative literature study method by analyzing various academic sources to identify the contribution of each theory to the deep learning approach. The results show that cognitive theories provide the basis for information processing strategies and metacognition; humanistic theories emphasize the importance of intrinsic motivation, personal values, and individual growth; while constructivistic theories support active, collaborative, and contextual learning. The synthesis of the three perspectives forms a comprehensive conceptual foundation for developing deep learning designs that are transformative and holistic. This research provides a significant conceptual contribution in the development of learning strategies that integrate cognitive, affective, and social aspects in a balanced manner